Potensi Pemanfaatan Hasil Pemeriksaan Berkala Bangunan Gedung dalam Penentuan Depresiasi Harga Bangunan Gedung Eksisting - Mochammad Hilmy; Herry Prabowo; Yudhiarma Yudhiarma (Politeknik Negeri Pontianak, 2020)
Over time, buildings are used to experience a decline in the physical quality of architectural, structural, mechanical and electrical components. To ensure its safety and functioning, periodic inspections of the building are required. The periodic technical inspection of buildings has been regulated in the Minister of Public Works Regulation No.16 / PRT / M / 2010. The results of the building inspection provide an overview of the physical condition and function of the building in detail and itemized by involving experts in building technical reviewers. The results of this examination show how much the percentage of physical degradation and function of the building under review has the potential to be used in assessing the price of existing buildings from an economic perspective. Thus the depreciation of building prices can be estimated. Depreciation value is a reduction in the value of fixed assets as a result of being used by the owner. This depreciation parameter is needed in an assessment of a property which is increasingly felt to be needed in various economic and development activities, including for loan guarantees, asset management, and appraisal for land acquisition for the purpose of building public facilities. The calculation of building prices that is carried out shows that the results of periodic inspections of buildings can be used to determine the depreciation of the price of the buildings under review.